Thiol Metabolism and Volatile Metabolome of Clostridioides difficile - Biwer, Peter; Neumann-Schaal, Meina; Henke, Petra; Jahn, Dieter; Schulz, Stefan (Frontiers in Microbiology, 2022)
Clostridioides diﬃcile (previously Clostridium diﬃcile) causes life-threatening gut infections. The central metabolism of the bacterium is strongly influencing toxin production and consequently the infection progress. In this context the composition and potential origin of the volatile metabolome was investigated, showing a large number of sulfur-containing volatile metabolites. GC/MS-based headspace analyses of growing C. difficile 630Δerm cultures identified 105 mainly sulfur-containing compounds responsible of the typical C. difficile odor. Major components were identified to be 2 methyl-1-propanol, 2-methyl-1-propanethiol, 2-methyl-1-butanethiol, 4-methyl-1-pentanethiol, and as well as their disulfides. Structurally identified were 64 sulfur containing volatiles. In order to determine their biosynthetic origin, the concentrations of the sulfur-containing amino acids methionine and cysteine were varied in the growth medium. The changes observed in the volatile metabolome profile indicated that cysteine plays an essential role in the formation of the sulfur-containing volatiles. We propose that disulfides are derived from cysteine via formation of cystathionine analogs, which lead to corresponding thiols. These thiols may then be oxidized to disulfides. Moreover, methionine may contribute to the formation of short-chain disulfides through integration of methanethiol into the disulfide biosynthesis. In summary, the causative agents of the typical C. difficile odor were identified and first hypotheses for their biosynthesis were proposed.